2023
DOI: 10.1097/ms9.0000000000000611
|View full text |Cite
|
Sign up to set email alerts
|

Surgical research in Colombia part 3: Authorship and publications of Colombian medical students in surgery in Colombian medical journals—cross-sectional study

Abstract: Introduction: Research training, scientific activity and publications are cornerstones of academic surgery. Knowing the activity and trends of medical students aspiring to become surgeons it allows to identify gaps and skills to be strengthened. Currently, there is no data on the authorship and scientific activity of medical students in surgery in Latin America and Colombia. Methods: A bibliometric cross-sectional study was carried out, in which the Col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
3

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 23 publications
(32 reference statements)
0
1
0
3
Order By: Relevance
“…The distribution of authors in academic publications is highly dependent on the region and field of study. According to a study conducted in Colombia, only 12 of the 32 territorial departments demonstrated a significant volume of academic publications in the field of surgery with students as authors (12).…”
Section: Discussionmentioning
confidence: 99%
“…The distribution of authors in academic publications is highly dependent on the region and field of study. According to a study conducted in Colombia, only 12 of the 32 territorial departments demonstrated a significant volume of academic publications in the field of surgery with students as authors (12).…”
Section: Discussionmentioning
confidence: 99%
“…Este estudio revela un panorama atractivo, original y relevante en la investigación en falla cardíaca, que puede ser utilizado por investigadores, grupos de investigación, instituciones estatales, universidades y sociedades científicas interesadas en evaluar lo que se ha investigado y lo que se debe investigar sobre la falla cardíaca. Considerando las brechas y el pluralismo en el conocimiento, así como las posibles colaboraciones basadas en instituciones e investigadores líderes en la región, el uso de recursos bibliométricos (33)(34)(35)(36) , es fundamental para diseñar una hoja de ruta basada en evidencia que considere la inversión, la producción y los resultados de indicadores en salud y ciencia.…”
Section: Referencias Bibliográficasunclassified
“…La bibliometría es una herramienta esencial para cuantificar y describir el comportamiento de la investigación científica, ampliamente utilizada en ciencias biomédicas (11) . Esta permite calcular el impacto de la producción científica y visualizar las redes de colaboración y la forma en que se realiza y publica la investigación, lo cual se debe correlacionar con la calidad y sistematización de la evidencia, para valorar brechas, pluralismo y relevancia en investigación médica (12)(13)(14) .…”
Section: Introductionunclassified
“…En Colombia, se describió el panorama de la investigación quirúrgica nacional 9,10 , no obstante, la aplicación de la meta-investigación quirúrgica para valorar objetivamente la calidad metodológica, de reporte o reproducibilidad de estudios en cirugía, es un nicho novedoso del que se desconoce mucho. Es interesante y pertinente, la creación de líneas o grupos de investigación dedicados a este campo, que sirvan como apoyo para complementar y evaluar constantemente la calidad de los estudios en cirugía que se realizan en el país.…”
unclassified